Review of Ischemic Heart Disease Patients admitted in Dhulikhel Hospital - Gurung, Ram Bahadur; Pant, Pankaj; Pokharel, Baburam; Koju, Rajendra; Bedi, TRS (Nepalese Heart Journal, 2013)
The ischaemic heart disease is one of the most common cause of preventable deaths. The number of deaths due to ischaemic heart disease has been reported to be on the rise in the low and middle income countries. Data on the prevalence and risk profile of ischaemic heart disease is scarce in Nepal. The aim of this study was to analyze the demographic and risk profile of patients with ischaemic heart disease admitted at Dhulikhel hospital. 115 patients in the period between 2008 to 2009 with the diagnosis of ischaemic heart disease were identified and analyzed. The mean age of patients with IHD was 62.9+/- 12.79 years and the youngest was aged 34 years. The number of male patients was greater (54.8%) than the females (45.2%). Among the risk factors hypertension and diabetes were more common in females, whereas smoking was more common in males. The study also showed more people with IHD came from rural than urban areas. In conclusion, the ischaemic heart disease is a rising public health problem affecting even the younger age groups and people from lower socioeconomic strata. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 1-4 DOI: http://dx.doi.org/10.3126/njh.v7i1.8493